2023
DOI: 10.3390/plants12112215
|View full text |Cite
|
Sign up to set email alerts
|

Survival Strategies of Duckweeds, the World’s Smallest Angiosperms

Abstract: Duckweeds (Lemnaceae) are small, simply constructed aquatic higher plants that grow on or just below the surface of quiet waters. They consist primarily of leaf-like assimilatory organs, or fronds, that reproduce mainly by vegetative replication. Despite their diminutive size and inornate habit, duckweeds have been able to colonize and maintain themselves in almost all of the world’s climate zones. They are thereby subject to multiple adverse influences during the growing season, such as high temperatures, ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 189 publications
1
15
0
1
Order By: Relevance
“…A common stress response in duckweeds is the premature detachment of fronds from the parent colony [ 57 ]. In our study, this separation was observed in the presence of highly toxic elements (e.g., Ag and Hg) and under the highest concentration treatments.…”
Section: Resultsmentioning
confidence: 99%
“…A common stress response in duckweeds is the premature detachment of fronds from the parent colony [ 57 ]. In our study, this separation was observed in the presence of highly toxic elements (e.g., Ag and Hg) and under the highest concentration treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Duckweeds present an interesting challenge for photoacclimation due to their floating habit across diverse sites. They have unusual frond anatomy which includes large air spaces for floating, non-functional stomata, and minimal photoassimilate export to the vasculature ( Shtein et al , 2017 ; Ziegler et al , 2023 ). Their rapid growth rate is usually assessed by clonal colony expansion rates rather than progressive (3D) canopy development and tropic responses toward light seen in other macrophytes.…”
Section: Introductionmentioning
confidence: 99%
“…Known for their high protein content (45.54% dry weight), duckweeds have become popular superfoods in Thailand (7). Not only do they have a promisingly high level of nutritional value, but they are also one of the fastest-growing plants under ideal environmental conditions; reproducing by vegetative propagation, called fronds ( 8).…”
Section: Introductionmentioning
confidence: 99%